The Primary Care Endocrinologist - Sanjay Kalra; Madhur Verma; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
Superficially, primary health care seems to have nothing in common with the esoteric science of endocrinology. Changing trends of disease prevalence have facilitated a reappraisal of this attitude. Comprehensive endocrine services are now needed at the primary care level. Endocrine specialists have already taken on the mantle of working as bariatric physicians. The future will see qualified endocrinologists working at primary care level, handling metabolic and hormonal diseases, along with comorbid conditions. This will be a welcome trend, both for public health and for the specialty’s growth.